Surface-modified gold powder, method for preparing the same, and use thereof

CN122999953APending Publication Date: 2026-10-30CHANGCHUN YONGGU TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611256010.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其中,微米级金粉(大于1μm)堆积性好,但烧结温度要求极高,难以在无压条件下实现致密连接;粒径小于50nm的纳米金粉烧结驱动力(表面能)大,有利于低温致密化;但纳米颗粒极易团聚,在浆料中分散困难,且堆积密度低,烧结时收缩应力大,易产生裂纹

Benefits of technology

[0017]本发明提供了一种表面修饰金粉,包括金纳米颗粒以及原位修饰在所述金纳米颗粒表面的短链有机配体;所述金纳米颗粒的平均粒径为100~500nm;所述短链有机配体的碳原子数为2~14,末端官能团为-SH和-NH2中的一种或两种;所述短链有机配体的完全分解/挥发温度为80~230℃。本发明通过控制金纳米颗粒的平均粒径,平衡纳米效应和微米优势,保证足够高的表面能提供低温烧结驱动力,同时又保证良好的颗粒级配和堆积密度,保证连接层良好的性能;采用含有特定末端官能团的短链有机配体进行原位修饰,可以与金纳米颗粒发生化学吸附或配位,使短链有机配体牢固锚定在金纳米颗粒表面,提高短链有机配体与金纳米颗粒的结合效果,提高制备、储存的稳定性;并且,短链有机配体具有适当的温度窗口,可以在室温稳定分散金纳米颗粒,在烧结时又能完全脱附、分解或挥发,避免有机配体残留对连接层的污染,提高连接层的导电、导热性能和机械性能。实施例的结果显示,本发明提供的表面修饰金粉烧结后所得连接层孔隙率低于5%,热导率高于190W/(m·K),剪切强度大于40MPa。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999953A_ABST
    Figure CN122999953A_ABST
Patent Text Reader

Abstract

The application provides a surface modified gold powder and a preparation method and application thereof, and belongs to the technical field of metal nanometer materials. The application balances nanometer effect and micron advantage by controlling the average particle size of gold nanoparticles, guarantees a high enough surface energy to provide a low-temperature sintering driving force, and guarantees good particle grading and bulk density to guarantee good performance of a connecting layer. A short-chain organic ligand containing a specific end functional group is used for in-situ modification, chemical adsorption or coordination can be generated between the short-chain organic ligand and the gold nanoparticles, the short-chain organic ligand is firmly anchored on the surface of the gold nanoparticles, the combination effect of the short-chain organic ligand and the gold nanoparticles is improved, the stability during preparation and storage is improved, the short-chain organic ligand has a proper temperature window, the gold nanoparticles can be stably dispersed at room temperature, the short-chain organic ligand can be completely desorbed, decomposed or volatilized during sintering, the pollution of the organic ligand residue to the connecting layer is avoided, and the conductive, heat-conductive performance and mechanical performance of the connecting layer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal nanomaterials technology, specifically relating to a surface-modified gold powder, its preparation method, and its application. Background Technology

[0002] With the rapid development of third-generation semiconductor (such as SiC and GaN) power devices and high-frequency optoelectronic devices, more stringent requirements have been placed on the interconnect materials between the internal chips and the substrate: higher thermal and electrical conductivity, stronger resistance to electromigration, excellent resistance to thermomechanical fatigue, and lower processing temperatures. Gold (Au), due to its exceptional chemical stability, excellent flexibility, and extremely high electrical and thermal conductivity, has become an ideal interconnect material.

[0003] Low-temperature sintering gold technology is a key technology for achieving high-reliability gold interconnects. The core of this technology is to use gold powder of nano or submicron size, and through a specific sintering process, to fuse the gold powder at a temperature far below the melting point of gold to form a dense gold interconnect layer.

[0004] The microscopic properties of gold powder directly determine the ease of sintering and the final performance. Among them, micron-sized gold powder (greater than 1 μm) has good packing properties, but requires extremely high sintering temperatures and is difficult to achieve dense bonding under pressureless conditions; nano-sized gold powder with a particle size of less than 50 nm has a large sintering driving force (surface energy), which is beneficial for low-temperature densification; however, nanoparticles are very prone to agglomeration, making dispersion in slurry difficult, and the packing density is low, resulting in high shrinkage stress during sintering and easy cracking.

[0005] To prevent the agglomeration of nano-gold powder, organic ligands can be modified on its surface. However, traditional long-chain polymer ligands (such as polyvinylpyrrolidone PVP) or strongly bound ligands have high decomposition temperatures during sintering, which can leave carbides and severely degrade the electrical, thermal and mechanical properties of the bonding layer. If ligands with too low decomposition temperatures are used, they are unstable during storage or slurry preparation, resulting in poor coating effect and causing gold powder agglomeration and sedimentation. Summary of the Invention

[0006] The purpose of this invention is to provide a surface-modified gold powder, its preparation method, and its application. The surface-modified gold powder provided by this invention is stable and does not settle during storage and preparation, leaves no carbide residue during sintering, and produces a low-porosity bonding layer with good electrical, thermal, and mechanical properties.

[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a surface-modified gold powder, comprising gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 100~500nm; the number of carbon atoms in the short-chain organic ligands is 2~14, and the terminal functional groups are one or both of -SH and -NH2; the complete decomposition / volatilization temperature of the short-chain organic ligands is 80~230℃.

[0008] Preferably, the short-chain organic ligand includes one or more of ethanethiol, propanethiol, hexanethiol, octanethiol, dodecanethiol, mercaptopropionic acid, cysteine, 11-mercapto-1-undecanol, n-butylamine, hexylamine, octylamine, ethylenediamine, and ethanolamine.

[0009] The present invention also provides a method for preparing the surface-modified gold powder described in the above technical solution, comprising: mixing a gold precursor solution and a short-chain organic ligand to obtain a mixed solution; adding a reducing agent to the mixed solution to carry out a reduction reaction to obtain surface-modified gold powder.

[0010] Preferably, the molar ratio of gold element to short-chain organic ligand in the gold precursor solution is (0.1~2):1.

[0011] Preferably, the reducing agent includes one or more of borohydrides, ascorbic acid, ascorbate, citric acid, citrate, polyphenolic compounds, monosaccharides, polyols, and sulfites.

[0012] Preferably, the temperature of the reduction reaction is 0~70℃.

[0013] Preferably, the reducing agent is added to the mixture in the form of an aqueous reducing agent solution.

[0014] Preferably, the concentration of the reducing agent in the reducing agent aqueous solution is 0.05~0.2mol / L.

[0015] This invention also provides the application of the surface-modified gold powder described above in the preparation of sintered gold conductive materials, including: The surface-modified gold powder is mixed with a solvent to obtain a gold paste; The gold paste is applied to the substrate, the chip is attached, and then sintering is performed; the sintering temperature is higher than the complete decomposition / volatilization temperature of the short-chain organic ligand.

[0016] Preferably, the sintering is pressureless sintering.

[0017] This invention provides a surface-modified gold powder, comprising gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 100~500nm; the number of carbon atoms in the short-chain organic ligands is 2~14, and the terminal functional groups are one or both of -SH and -NH2; the complete decomposition / volatilization temperature of the short-chain organic ligands is 80~230℃. This invention balances the nano-effects and micro-advantages by controlling the average particle size of gold nanoparticles, ensuring sufficiently high surface energy to provide driving force for low-temperature sintering, while simultaneously guaranteeing good particle size distribution and packing density to ensure excellent performance of the bonding layer. In-situ modification with short-chain organic ligands containing specific terminal functional groups allows for chemical adsorption or coordination with gold nanoparticles, firmly anchoring the short-chain organic ligands to the surface of the gold nanoparticles, improving the binding effect between the short-chain organic ligands and gold nanoparticles, and enhancing the stability during preparation and storage. Furthermore, the short-chain organic ligands possess an appropriate temperature window, allowing for stable dispersion of gold nanoparticles at room temperature, and complete desorption, decomposition, or volatilization during sintering, avoiding contamination of the bonding layer by residual organic ligands, and improving the electrical, thermal, and mechanical properties of the bonding layer. Results from the embodiments show that the bonding layer obtained after sintering the surface-modified gold powder provided by this invention has a porosity of less than 5%, a thermal conductivity greater than 190 W / (m·K), and a shear strength greater than 40 MPa. Attached Figure Description

[0018] Figure 1 This is a TEM image of the surface-modified gold powder provided in Embodiment 1 of the present invention; Figure 2 The TGA curve of the surface-modified gold powder provided in Embodiment 1 of the present invention; Figure 3 This is a TEM image of the surface-modified gold powder provided in Embodiment 2 of the present invention; Figure 4 The TGA curve of the surface-modified gold powder provided in Embodiment 2 of the present invention; Figure 5 This is a TEM image of the surface-modified gold powder provided in Comparative Example 2 of the present invention; Figure 6 This is a TEM image of the surface-modified gold powder provided in Comparative Example 3 of the present invention; Figure 7 This is a SEM image of the gold paste prepared from the surface-modified gold powder and sintered according to Embodiment 1 of the present invention. Figure 8 This is a SEM image of the gold paste prepared from the surface-modified gold powder and sintered according to Embodiment 2 of the present invention. Figure 9 SEM image of the gold paste prepared from the surface-modified gold powder provided in Comparative Example 1 of this invention after sintering; Figure 10SEM image of the gold paste prepared from the surface-modified gold powder provided in Comparative Example 2 of this invention after sintering; Figure 11 SEM image of the gold paste prepared from the surface-modified gold powder provided in Comparative Example 3 of this invention after sintering; Figure 12 SEM image of the gold paste prepared from the surface-modified gold powder provided in Comparative Example 4 of this invention after sintering; Figure 13 This is a SEM image of the gold paste prepared from the surface-modified gold powder provided in Comparative Example 5 of the present invention after sintering. Detailed Implementation

[0019] All raw materials used in this invention are not particularly restricted in their source; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.

[0020] There are no particular restrictions on the purity of any raw materials used in this invention. However, this invention preferably uses raw materials with high purity or those of conventional purity in the field of nano-metals.

[0021] This invention provides a surface-modified gold powder, comprising gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 100~500nm; the number of carbon atoms in the short-chain organic ligands is 2~14, and the terminal functional groups are one or both of -SH and -NH2; the complete decomposition / volatilization temperature of the short-chain organic ligands is 80~230℃.

[0022] The surface-modified gold powder provided by this invention includes gold nanoparticles.

[0023] In this invention, the average particle size of the gold nanoparticles is 100-500 nm, preferably 100-300 nm; as one embodiment of this invention, the average particle size of the gold nanoparticles can be 120 nm, 150 nm, 180 nm, 200 nm, 240 nm, 280 nm, 320 nm, 350 nm, 400 nm, or 450 nm. The average particle size of the gold nanoparticles within the above range provides a large specific surface area, which can provide significant sintering driving force; and a high mobility, enabling rapid migration through mechanisms such as surface diffusion and grain boundary diffusion, achieving neck growth and densification between particles; it can also balance the nano-effect and the micron advantage, ensuring sufficiently high surface energy to provide low-temperature sintering driving force, while also ensuring good packing density and good performance of the bonding layer.

[0024] In another embodiment of the present invention, the gold nanoparticles are composed of at least two components with different particle sizes, forming a multi-level particle size distribution system to improve particle packing density and promote low-temperature sintering densification. Specifically, the gold nanoparticles include a first component and a second component. The average particle size of the first component is 200-350 nm, accounting for 60-80% of the total mass of the gold particles; the average particle size of the second component is 80-150 nm, accounting for 20-40% of the total mass of the gold particles. By controlling the average particle size within the above range and adopting the above particle size distribution, it is possible to utilize smaller particle sizes to provide higher surface energy and sintering driving force, and to utilize larger particle sizes to construct a framework and improve packing density, thereby achieving rapid neck growth, densification, and the formation of a high-performance metal bonding layer between particles under low-temperature conditions.

[0025] In one embodiment of the present invention, the particle size distribution of the gold nanoparticles is log-normal, and the polydispersity index (PDI) is not greater than 0.25, or may be not greater than 0.15.

[0026] In one embodiment of the present invention, the gold nanoparticles are spherical or near-spherical. Statistical analysis of at least 200 particles using a transmission electron microscope reveals that the ratio of the major axis to the minor axis (length-to-width ratio) of the gold nanoparticles is 1.0 to 1.3, or 1.0 to 1.15, and the roundness is not less than 0.85, or not less than 0.90. Using spherical or near-spherical gold nanoparticles helps reduce interparticle contact resistance, improves particle packing density and surface diffusion uniformity, thereby promoting neck growth and densification during low-temperature sintering.

[0027] The surface-modified gold powder provided by the present invention includes short-chain organic ligands in situ modified on the surface of the gold nanoparticles.

[0028] Short-chain organic ligands form an organic molecular layer on the surface of gold nanoparticles. Through steric hindrance, this effectively prevents the gold nanoparticles from coming into close contact with each other and from irreversibly agglomerating in the slurry system, ensuring that the gold powder can maintain a uniform and stable dispersion in the slurry for a long time.

[0029] In this invention, the short-chain organic ligand has 2 to 14 carbon atoms, preferably 5 to 10. As one embodiment of this invention, the short-chain organic ligand may have 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, or 13 carbon atoms. When the number of carbon atoms in the short-chain organic ligand is within the above range, it exhibits moderate thermal stability and a low decomposition or volatilization temperature. During sintering, it can break and decompose on the surface of the gold nanoparticles and completely escape in the form of gaseous small molecules, avoiding residual carbides or organic impurities that could affect the performance of the bonding layer. This achieves in-situ cleaning of the gold nanoparticle surface, creating pure interfacial conditions for subsequent direct contact and diffusion between gold atoms.

[0030] In this invention, the terminal functional groups of the short-chain organic ligands are one or both of -SH and -NH2. -SH can form Au-S bonds with gold nanoparticles, enabling the short-chain organic ligands to be firmly adsorbed onto the surface of the gold nanoparticles, ensuring the stability of the short-chain organic ligands during slurry preparation and storage, and preventing ligand desorption that could lead to aggregation of gold nanoparticles. The lone pair electrons of the nitrogen atom in -NH2 can coordinate with gold, providing sufficient adsorption force, and the thermal decomposition products are easily volatilized, resulting in a pure linking layer.

[0031] In this invention, the complete decomposition / volatilization temperature of the short-chain organic ligand is 80~230℃, preferably 150~200℃. As one embodiment of this invention, the complete decomposition / volatilization temperature of the short-chain organic ligand can be 100℃, 120℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, or 220℃. Having the complete decomposition / volatilization temperature of the short-chain organic ligand within the above range ensures that a relatively low sintering temperature is sufficient to completely decompose / volatilize the short-chain organic ligand, avoiding excessively high sintering temperatures that could negatively impact component performance.

[0032] In this invention, the short-chain organic ligand preferably includes one or more of the following: ethanethiol, propanethiol, hexanethiol, octylthiol, dodecylthiol, mercaptopropionic acid, cysteine, 11-mercapto-1-undecanol, n-butylamine, hexylamine, octylamine, ethylenediamine, and ethanolamine. All of the above compounds can be firmly adsorbed onto the surface of gold nanoparticles and have low thermal decomposition temperatures or boiling points, allowing for complete decomposition or volatilization at relatively low temperatures.

[0033] This invention balances the nano-effects and micro-advantages by controlling the average particle size of gold nanoparticles, ensuring sufficiently high surface energy to provide driving force for low-temperature sintering, while also guaranteeing good particle size distribution and packing density to ensure good performance of the bonding layer. In-situ modification with short-chain organic ligands containing specific terminal functional groups allows for chemical adsorption or coordination with gold nanoparticles, firmly anchoring the short-chain organic ligands to the surface of the gold nanoparticles, improving the binding effect between the short-chain organic ligands and the gold nanoparticles, and enhancing the stability during preparation and storage. Furthermore, the short-chain organic ligands have an appropriate temperature window, allowing for stable dispersion of gold nanoparticles at room temperature, and complete desorption, decomposition, or volatilization during sintering, avoiding contamination of the gold nanoparticles by the organic ligands and improving the electrical conductivity, thermal conductivity, and mechanical properties of the bonding layer.

[0034] The present invention also provides a method for preparing the surface-modified gold powder described in the above technical solution, comprising: mixing a gold precursor solution and a short-chain organic ligand to obtain a mixed solution; adding a reducing agent to the mixed solution to carry out a reduction reaction to obtain surface-modified gold powder.

[0035] In this invention, the short-chain organic ligands are pre-mixed with the gold precursor solution, and in-situ surface modification of gold nanoparticles is achieved after the addition of a reducing agent. The short-chain organic ligands adsorb onto the particle surface during gold nucleation, selectively passivating specific crystal planes and inhibiting anisotropic growth, which is beneficial for obtaining spherical or near-spherical gold nanoparticles. Simultaneously, the short-chain organic ligands can adjust the nucleation-to-growth rate ratio, allowing particles to grow to an average particle size of 100-500 nm under controlled conditions, forming a narrower particle size distribution. Furthermore, the in-situ formed short-chain surface modification layer provides appropriate steric hindrance to prevent particle agglomeration, and this modification layer can be removed during subsequent low-temperature sintering, exposing the high surface energy gold surface. This provides sufficient sintering driving force for surface diffusion, grain boundary diffusion, and neck growth between particles, which is beneficial for obtaining a dense connecting layer.

[0036] In one embodiment of the present invention, the gold precursor solution may be obtained by dissolving chloroauric acid in a solvent; the solvent may be water and / or an alcohol solvent, and the alcohol solvent may be ethanol; when the solvent is a mixture of water and alcohol solvent, the volume ratio of water to alcohol solvent may be 1:1.

[0037] In one embodiment of the present invention, the concentration of chloroauric acid in the gold precursor solution can be 0.001~0.1 mol / L.

[0038] In this invention, the preferred molar ratio of gold element to short-chain organic ligand in the gold precursor solution is (0.1~2):1, more preferably (0.5~1):1. As one embodiment of this invention, the molar ratio of gold element to short-chain organic ligand in the gold precursor solution can be 0.2:1, 0.4:1, 0.5:1, 0.6:1, 2:3, 0.75:1, 1:1, 1.25:1, 1.5:1, or 1.8:1. When the molar ratio of gold element to short-chain organic ligand in the gold precursor solution is within the above range, the short-chain organic ligand can fully modify the gold nanoparticles, further improving the stability of the surface-modified gold powder.

[0039] In one embodiment of the present invention, the mixing can be carried out under stirring conditions, the stirring can be magnetic stirring, and the stirring time can be 30 minutes.

[0040] In this invention, the reducing agent preferably includes one or more of the following: borohydrides, ascorbic acid, ascorbate, citric acid, citrate, polyphenolic compounds, monosaccharides, polyols, and sulfites. All of the above compounds can reduce chloroauric acid to elemental gold.

[0041] In this invention, the reducing agent is added to the mixture in the form of an aqueous reducing agent solution. Adding the reducing agent in the form of an aqueous reducing agent solution helps stabilize the reaction rate and improves the size uniformity of the gold nanoparticles.

[0042] In this invention, the concentration of the reducing agent in the aqueous reducing agent solution is preferably 0.05~0.2 mol / L, more preferably 0.1~0.15 mol / L. A concentration of the reducing agent in the aqueous reducing agent solution within the above range is beneficial for stabilizing the reaction rate and improving the size uniformity of the gold nanoparticles.

[0043] In one embodiment of the present invention, the reducing agent aqueous solution can be added dropwise to the mixture. When the reducing agent is a strong reducing agent (such as sodium borohydride), the reducing agent aqueous solution is added slowly dropwise over a period of not less than 50 seconds, so that the gold ions in the reaction system instantly reach a high supersaturation, inducing explosive nucleation, which is beneficial for obtaining gold nanoparticles with small particle size and narrow size distribution. When the reducing agent is a weak or moderately strong reducing agent (such as sodium citrate, ascorbic acid, or tartaric acid), the reducing agent aqueous solution is added rapidly dropwise or in a single injection, with a dropwise time not exceeding 30 seconds, specifically 5-15 seconds, so that the reduction reaction rate matches the nucleation and growth process, which is beneficial for obtaining gold nanoparticles with an average particle size in the range of 100-500 nm and good monodispersity. By controlling the combination of the type of reducing agent and the dropwise addition rate, the nucleation density and subsequent growth degree of the gold nanoparticles can be effectively adjusted, thereby achieving precise control of the target particle size range and narrow particle size distribution.

[0044] In one embodiment of the present invention, when adding the reducing agent aqueous solution, the temperature of the mixture is controlled between 0 and 40°C. Specifically, the mixture can be placed in an ice bath or the process can be carried out at room temperature. The addition of the reducing agent aqueous solution can be carried out under stirring conditions. Lowering the temperature of the mixture when adding the reducing agent aqueous solution can reduce the rate of the reduction reaction, reduce the formation of crystal nuclei, and increase the particle size of the gold nanoparticles.

[0045] In one embodiment of the present invention, the reducing agent can be 1.5 to 6 times the theoretical consumption amount to ensure complete reaction of chloroauric acid; the theoretical consumption amount is calculated based on the amount of chloroauric acid and according to the stoichiometric ratio.

[0046] In this invention, the temperature of the reduction reaction is preferably 0~70℃, more preferably 25~60℃; as one embodiment of the invention, the temperature of the reduction reaction can be 10℃, 20℃, 25℃, 30℃, 40℃, 50℃, or 60℃; the temperature of the reduction reaction can be controlled by a water bath; as another embodiment of the invention, the reduction reaction can be carried out at room temperature. A temperature within the above range is beneficial for controlling the reaction rate and ensuring stable growth of gold nanoparticles.

[0047] In one embodiment of the present invention, after the reducing agent aqueous solution is added dropwise, the reaction can continue for 0.5 to 4 hours to allow the raw materials to react fully.

[0048] In one embodiment of the present invention, after the reduction reaction is completed, the obtained product can be subjected to solid-liquid separation. The obtained solid product is washed and dried to obtain surface-modified gold powder. In one embodiment of the present invention, the solid-liquid separation can be centrifugation; the centrifugation speed can be 12000 rpm, and the centrifugation time can be 15 min; the solvent used for washing can be a solvent compatible with short-chain organic ligands, specifically ethanol or acetone; the number of washings can be 3 to 5 times; the drying can be vacuum drying or inert atmosphere drying; the drying temperature can be 40°C, and the time can be 12 h.

[0049] The preparation method provided by this invention is simple, uses mild parameters, requires no special equipment, and is conducive to industrial production.

[0050] This invention also provides the application of the surface-modified gold powder described in the above-described technical solutions or the surface-modified gold powder prepared by the preparation method described in the above-described technical solutions in the preparation of sintered gold conductive materials, including: The surface-modified gold powder is mixed with a solvent to obtain a gold paste; The gold paste is applied to the substrate, the chip is attached, and then sintering is performed; the sintering temperature is higher than the complete decomposition / volatilization temperature of the short-chain organic ligand.

[0051] In one embodiment of the present invention, the solvent may be terpineol; the mass ratio of the surface-modified gold powder to the solvent may be 85:15.

[0052] In one embodiment of the present invention, the gold paste can be applied by dotting.

[0053] The present invention does not have a particular limitation on the amount of gold paste applied; any amount known to those skilled in the art can be used.

[0054] The present invention does not impose any particular limitation on the method of attaching the chip; any method known to those skilled in the art can be used.

[0055] In this invention, the sintering is preferably pressureless sintering. Pressureless sintering means that no additional pressure is applied during sintering; pressureless sintering can prevent pressure from damaging the chip.

[0056] In this invention, the sintering temperature is higher than the complete decomposition / volatilization temperature of the short-chain organic ligands. This temperature ensures the complete decomposition or volatilization of the short-chain organic ligands modified on the surface of the gold nanoparticles, avoiding residues.

[0057] In one embodiment of the present invention, the sintering temperature can be 240~300℃; the sintering heating method can be gradient heating, which can be heating to 180℃ at a rate of 5℃ / min, holding for 20min, and then heating to the sintering temperature at a rate of 3℃ / min, holding for 60min.

[0058] The application provided by this invention can reduce the porosity of the bonding layer and improve its thermal conductivity, electrical conductivity and mechanical properties.

[0059] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0060] Example 1 A surface-modified gold powder comprises gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 120 nm (D10 is 90~100 nm, D50 is 115~125 nm, D90 is 140~155 nm), and the particles are spherical (particle aspect ratio is 1.0~1.15, and roundness is not less than 0.90); the short-chain organic ligand is octylthiol.

[0061] The preparation method is as follows: 0.5 mmol of chloroauric acid was dissolved in 200 mL of ethanol / water (volume ratio 1:1); 0.75 mmol of octyl mercaptan was added, and the mixture was magnetically stirred at room temperature (25 °C) for 30 min. Under ice-water bath and vigorous stirring (500 rpm), 20 mL of 0.1 mol / L sodium borohydride aqueous solution was added dropwise. After the addition was completed in 2 min, the ice bath was removed, and the reaction was continued at room temperature for 2 h. The reaction solution changed from light yellow to dark reddish-brown. The resulting colloidal solution was centrifuged at 12000 rpm for 15 min, the precipitate was collected, washed three times with ethanol, and finally the product was dried in a vacuum oven at 40 °C for 12 h to obtain gold powder with surface modified octyl mercaptan.

[0062] The obtained gold powder was observed using a transmission electron microscope, and TEM images were obtained, such as... Figure 1 As shown. For Figure 1 Analysis revealed that the average particle size of the gold powder was 120 nm.

[0063] The obtained gold powder was subjected to thermogravimetric analysis, and the TGA curve was obtained as follows: Figure 2 As shown. By Figure 2 It can be seen that the gold powder is stable at 220℃, indicating that the octylthiol modified on the surface of the gold nanoparticles is completely decomposed.

[0064] Example 2 A surface-modified gold powder is composed of gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 280 nm, and they are spherical particles; the short-chain organic ligand is hexylamine.

[0065] The preparation method is as follows: 1.0 mmol of chloroauric acid was dissolved in 200 mL of deionized water; 2.0 mmol of hexylamine was added, and the mixture was magnetically stirred at room temperature (25 °C) for 30 min. While stirring, 30 mL of 0.1 mol / L ascorbic acid aqueous solution was added dropwise. After the addition was completed in 10 s, the mixture was heated to reflux in a water bath at 60 °C for 1 h. During the dropwise addition, the reaction solution gradually changed from light yellow to wine red. The resulting colloidal solution was centrifuged at 12000 rpm for 15 min, the precipitate was collected, washed twice with water and once with ethanol, and finally the product was dried in a vacuum oven at 40 °C for 12 h to obtain gold powder with surface-modified hexylamine.

[0066] The obtained gold powder was observed using a transmission electron microscope, and TEM images were obtained, such as... Figure 3 As shown. For Figure 3 Analysis revealed that the average particle size of the gold powder was 280 nm.

[0067] The obtained gold powder was subjected to thermogravimetric analysis, and the TGA curve was obtained as follows: Figure 4 As shown. By Figure 4 It can be seen that the gold powder is stable at 200℃, indicating that the hexylamine modified on the surface of the gold nanoparticles is completely decomposed.

[0068] Comparative Example 1 Commercially available surface-modified gold powder (Aladdin G475858) with an average particle size of 300 nm, surface-modified with polyvinylpyrrolidone (PVP).

[0069] Comparative Example 2 A surface-modified gold powder is composed of gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 1.5 μm, and they are spherical particles; the short-chain organic ligand is hexylamine.

[0070] The preparation method is as follows: Dissolve 0.5 mmol of chloroauric acid (HAuCl4·3H2O) in 200 mL of deionized water; add 1.0 mmol of hexylamine and stir magnetically at room temperature (25℃) for 30 min. While stirring, add 20 mL of 0.05 mol / L ascorbic acid aqueous solution (with weak reducing power) dropwise over a period of 20 min. After the addition is complete, no heating is performed. Instead, the reaction is stirred for 12 hours at room temperature (25°C) to allow the small particles to dissolve fully and gold atoms to deposit on the surface of the large particles. The obtained colloidal solution was centrifuged at 3000 rpm for 10 min, the precipitate was collected, washed twice with water and once with ethanol, and finally the product was dried in a vacuum oven at 40℃ for 12 h to obtain large-sized gold powder with surface-modified hexylamine.

[0071] The obtained gold powder was observed using a transmission electron microscope, and TEM images were obtained, such as... Figure 5 As shown in the image, analysis of the TEM image revealed that the average particle size of the gold powder was 1.5 μm.

[0072] Comparative Example 3 A surface-modified gold powder is composed of gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 50 nm, and they are spherical particles; the short-chain organic ligand is hexylamine.

[0073] The preparation method is as follows: 2.0 mmol of chloroauric acid (HAuCl4·3H2O) is dissolved in 200 mL of deionized water; 4.0 mmol of hexylamine is added, and the mixture is magnetically stirred for 30 min in an ice bath (0~5℃); Under vigorous stirring, inject 10 mL of an ice-water mixture containing 6.0 mmol sodium borohydride (NaBH4) in a single, rapid injection (injection time 30 s). After injection, the reaction solution immediately changed from light yellow to brownish-yellow, and the reaction was continued to be stirred for 30 minutes under ice bath conditions; The obtained colloidal solution was centrifuged at 12,000 rpm for 15 min, the precipitate was collected, washed twice with water and once with ethanol, and finally the product was dried in a vacuum oven at 40 °C for 12 h to obtain small-sized gold powder with surface-modified hexylamine.

[0074] The obtained gold powder was observed using a transmission electron microscope, and TEM images were obtained, such as... Figure 6 As shown in the image, analysis of the TEM image revealed that the average particle size of the gold powder was 50 nm.

[0075] Comparative Example 4 A surface-modified gold powder is composed of gold nanoparticles and short-chain organic ligands in situ modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 300 nm, and they are spherical particles; the short-chain organic ligands are didecyl sulfide.

[0076] The preparation method is the same as that of Comparative Example 2, except that hexylamine is replaced with an equal amount of dialcyl sulfide.

[0077] Comparative Example 5 A surface-modified gold powder is composed of gold nanoparticles and short-chain organic ligands modified on the surface of the gold nanoparticles; the average particle size of the gold nanoparticles is 120 nm, and they are spherical particles; the short-chain organic ligands are hexylamine.

[0078] The preparation method is as follows: 1.0 mmol of chloroauric acid was dissolved in 200 mL of deionized water and magnetically stirred at room temperature for 30 min. While stirring, 30 mL of 0.1 mol / L ascorbic acid aqueous solution was added dropwise. After the addition was completed in 10 min, the mixture was heated to reflux in a water bath at 60 °C for 1 h. During the dropwise addition, the reaction solution gradually changed from light yellow to wine red. 2.0 mmol of hexylamine was added and stirred for 1 h. The resulting colloidal solution was centrifuged at 12000 rpm for 15 min, the precipitate was collected, washed twice with water and once with ethanol, and finally the product was dried in a vacuum oven at 40 °C for 12 h to obtain gold powder with surface modified hexylamine.

[0079] Application examples The surface-modified gold powder provided in Examples 1-2 and Comparative Examples 1-4 was mixed with terpineol at a mass ratio of 85:15 and ultrasonically treated for 1 hour to obtain gold paste. Apply gold paste to the gold-plated substrate and attach the chip. Heat the substrate to 180°C at a rate of 5°C / min and hold for 20 minutes. Then heat the substrate to 250°C at a rate of 3°C / min and hold for 60 minutes.

[0080] Performance tests were performed on each connection layer, and the test results are recorded in Table 1.

[0081] The porosity testing method is as follows: After resin embedding, grinding, and polishing, the sintered bonding layer sample is subjected to cross-sectional backscattered electron imaging at 2000-5000x magnification along a cross-sectional direction perpendicular to the bonding interface. Figures 7-13 As shown; the image is processed to distinguish between pores (dark areas) and the metal substrate (bright areas), and the porosity (%) is calculated according to the formula: Porosity (%) = (total area of ​​pore pixels / total area of ​​field of view) × 100%; The shear strength test method is as follows: The sintered silver frame is attached to the stage. The cutting head is positioned close to the side root of the chip, with its height parallel to the substrate. The shear height, test speed, and safety load are set. The cutting head is advanced horizontally at a constant speed, "scooping" towards the chip parallel to the silver frame. The pushing force when the chip is pushed away is recorded.

[0082] The thermal conductivity test method is as follows: Sintered gold paste is printed onto a flat polytetrafluoroethylene (PTFE) substrate, sintered according to the actual process, and the sintered gold sheet is polished into a circular disc with a diameter of 12.7 mm and a thickness of 1-3 mm, with a parallelism of <0.01 mm on both sides. A thin graphite layer is sprayed onto the back side to obtain the test sample. The test sample is placed in a sample holder, ensuring that the laser, the test sample, and the infrared detector are coaxial. Under an inert gas environment, a laser pulse irradiates the back side of the test sample, and the infrared detector records the temperature rise curve of the front side. The software calculates the thermal diffusivity based on the temperature rise half-life, and combines it with the specific heat capacity and density to obtain the thermal conductivity. Thermal conductivity = thermal diffusivity * specific heat capacity * density.

[0083] The volume resistivity test method is as follows: use a four-probe resistance tester to measure the resistance value R of the sintered layer at room temperature, and combine it with the sample thickness t and the effective test area S to calculate the resistivity ρ according to the formula: ρ=R·t / S, and the conductivity σ=1 / ρ; each sample is tested no less than 3 times and the average value is taken.

[0084] Table 1. Performance test records of bonding layers obtained with different surface-modified gold powders.

[0085] The bonding layer obtained after sintering in Comparative Example 1 showed obvious black residue, which was analyzed to be incompletely decomposed PVP carbonization products.

[0086] As can be seen from Table 1, the average particle size of gold nanoparticles directly affects the performance of the bonding layer. When the particle size is too large, the porosity, electrical conductivity, thermal conductivity and mechanical properties of the bonding layer all decrease significantly. The modifiers on the surface of gold nanoparticles also directly affect the performance of the bonding layer. In Comparative Example 1, PVP was used as an organic ligand, and its decomposition was incomplete after sintering, which affected the performance of the bonding layer.

[0087] As can be seen from the above embodiments, the surface-modified gold powder provided by the present invention leaves no residue after sintering, and the bonding layer has excellent performance.

[0088] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A surface-modified gold powder, comprising gold nanoparticles and a short-chain organic ligand in situ modified on the surface of the gold nanoparticles; wherein the average particle size of the gold nanoparticles is 100-500 nm; the short-chain organic ligand has 2-14 carbon atoms and the terminal functional group is one or both of -SH and -NH2; and the complete decomposition / volatilization temperature of the short-chain organic ligand is 80-230 °C.

2. The surface-modified gold powder according to claim 1, characterized in that, The short-chain organic ligands include one or more of ethanethiol, propanethiol, hexanethiol, octanethiol, dodecanethiol, mercaptopropionic acid, cysteine, 11-mercapto-1-undecanol, n-butylamine, hexylamine, octylamine, ethylenediamine, and ethanolamine.

3. The method for preparing the surface-modified gold powder according to claim 1 or 2, characterized in that, include: A gold precursor solution and a short-chain organic ligand are mixed to obtain a mixture; a reducing agent is added to the mixture to carry out a reduction reaction to obtain surface-modified gold powder.

4. The preparation method according to claim 3, characterized in that, The molar ratio of gold element to short-chain organic ligand in the gold precursor solution is (0.1~2):

1.

5. The preparation method according to claim 3, characterized in that, The reducing agent includes one or more of borohydrides, ascorbic acid, ascorbate, citric acid, citrate, polyphenolic compounds, monosaccharides, polyols, and sulfites.

6. The preparation method according to claim 5, characterized in that, The reduction reaction is carried out at a temperature of 0~70℃.

7. The preparation method according to claim 3, characterized in that, The reducing agent is added to the mixture in the form of an aqueous solution of reducing agent.

8. The preparation method according to claim 7, characterized in that, The concentration of the reducing agent in the aqueous solution is 0.05~0.2 mol / L.

9. The application of the surface-modified gold powder according to claim 1 or 2, or the surface-modified gold powder prepared by the preparation method according to any one of claims 3 to 8, in the preparation of sintered gold conductive materials, characterized in that, include: The surface-modified gold powder is mixed with a solvent to obtain a gold paste; The gold paste is applied to the substrate, the chip is attached, and then sintering is performed. The sintering temperature is higher than the complete decomposition / volatilization temperature of the short-chain organic ligand.

10. The application according to claim 9, characterized in that, The sintering is pressureless sintering.